STUNTING DISASTER RISK REDUCTION EFFORTS IN INDONESIA THROUGH RISK COMMUNICATION - Mira Hasti Hasmira (Jurnal Ranah Komunikasi, 2023)
Indonesia's inclusion in the prevalence of stunting by WHO poses an extraordinary threat to the future growth of the nation's children. The purpose of writing this article is to describe messages in risk communication that must be conveyed in disaster risk management efforts. Stunting can be categorized as a disaster, especially non-natural disasters because it has a psychological impact and is a threat to the growth of babies in Indonesia. This paper uses qualitative methods, to be a precise literature study in data collection. found that, In efforts to reduce disaster risk (DRR), three factors serve as a reference and must be studied to determine the stages of disaster management, namely threat, vulnerability, and capacity for stunting. This is the main message and communication of the risk of stunting in Indonesia.